Growth Asymmetry, Head Circumference and Neurodevelopmental Outcomes in Infants with Single Ventricles - Miller, Thomas A. (J Pediatr, 2015)
OBJECTIVES: To assess the variability in asymmetric growth and its association with neurodevelopment in infants with single ventricles (SV). STUDY DESIGN: We analyzed weight for age z-score (WAZ) minus head circumference for age z-score (HCAZ), relative head growth (cm/kg), along with individual growth variables in subjects prospectively enrolled in the Infant Single Ventricle (ISV) trial. Associations between growth indices and scores on the Psychomotor Developmental Index (PDI) and Mental Developmental Index (MDI) of the Bayley Scales of Infant Development-II (BSID-II) at 14 months were assessed. RESULTS: Of the 230 subjects enrolled in the ISV trial, complete growth data and BSID-II scores were available in 168 (73%). Across the cohort, indices of asymmetric growth varied widely at enrollment and before superior cavopulmonary connection (SCPC) surgery. BSID-II scores were not associated with these asymmetry indices. In bivariate analyses, greater pre-SCPC HCAZ correlated with higher MDI (r=0.21, p=0.006) and PDI (r=0.38, p<0.001) and a greater HCAZ increase from enrollment to pre-SCPC with higher PDI (r=0.15, p=0.049). In multivariable modeling, pre-SCPC HCAZ was an independent predictor of PDI (p=0.03), but not MDI. CONCLUSIONS: In infants with SV, growth asymmetry was not associated with neurodevelopment at 14 months, but pre-SCPC HCAZ was associated with PDI. Asymmetric growth, important in other high risk infants, is not a brain sparing adaptation in infants with SV. TRIAL REGISTRATION: Clinicaltrials.gov: NCT00113087